2008
DOI: 10.1158/1078-0432.ccr-08-0679
|View full text |Cite
|
Sign up to set email alerts
|

Protein Expression Profiling in Esophageal Adenocarcinoma Patients Indicates Association of Heat-Shock Protein 27 Expression and Chemotherapy Response

Abstract: Purpose: To identify pretherapeutic predictive biomarkers in tumor biopsies of patients with locally advanced esophageal adenocarcinomas treated with neoadjuvant chemotherapy, we used an explorative proteomic approach to correlate pretherapeutic protein expression profiles with tumor response to neoadjuvant chemotherapy. Experimental Design: Thirty-four patients with locally advanced esophageal adenocarcinomas who received neoadjuvant platin/5-fluorouracil^based chemotherapy before surgical resection were enro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…HSP27 has been reported to be overexpressed and associated with poor prognosis in many human cancers, including breast, rectal, gastric, lung, liver and prostate cancers (33)(34)(35)(36). Contrary to the findings in most cancers, in human esophageal squamous cell carcinoma (HESCC), the expression of HSP27 was low, and this low expression was correlated with poor prognosis (37,38).…”
Section: Discussionmentioning
confidence: 97%
“…HSP27 has been reported to be overexpressed and associated with poor prognosis in many human cancers, including breast, rectal, gastric, lung, liver and prostate cancers (33)(34)(35)(36). Contrary to the findings in most cancers, in human esophageal squamous cell carcinoma (HESCC), the expression of HSP27 was low, and this low expression was correlated with poor prognosis (37,38).…”
Section: Discussionmentioning
confidence: 97%
“…To identify predictive biomarkers, Langer et al analyzed pretherapeutic protein expression profiles in tumor biopsy specimens of 34 EAC patients treated with neoadjuvant chemotherapy [56]. The authors found that the levels of cellular stress response-associated Hsp27 and Hsp60, glucose-regulated proteins 94 and 78, and a number of cytoskeletal proteins differed significantly between responders and nonresponders.…”
Section: Eacmentioning
confidence: 99%
“…Such protection is conferred by enhanced proliferation [11,13] and suppressed apoptosis in cancer cells [14][15][16]. Increased expression of Hsp27 is found in various cancer types [9,10,[17][18][19][20][21], supporting the hypothesis that Hsp27 is a therapeutic target in a broad spectrum of cancers. In fact, several agents that modulate Hsp27 have already exhibited promising anti-tumor activity in preclinical models of a variety of tumors, particularly those expressing high levels of Hsp27 [17,22,23].…”
Section: An Open Access Publishermentioning
confidence: 91%